Investigation of heterogeneous sulfonated graphene oxide to hydrolyze cellulose and produce dark fermentative biohydrogen using Enterobacter aerogenes. (June 2020) - Tondro, Hadiseh; Zilouei, Hamid; Zargoosh, Kiomars; Bazarganipour, Mehdi
Graphical abstract: Highlights: Sulfonated graphene oxide with high acid density of 4.63 mmol/g was synthesized. Potential of solid acid catalytic hydrolysates was investigated for H2 fermentation. Total reducing sugars yield 351.28 mg/g microcrystalline cellulose was obtained. Glucose yield 237.41 mg/g cellulose was obtained with a low mass ratio of catalyst. Maximum hydrogen production rate of 7.7 mL/g/h was achieved in 20 h. Abstract: The main aim of this work was investigating the potential of sulfonated graphene oxide (sGO) for hydrolysis of cellulosic substrates and dark fermentative hydrogen production from obtained hydrolysates using E. aerogenes . Sulfonation of graphene oxide was performed using chlorosulfonic acid which showed a high acid density of 4.63 mmol/g. Influence of the reaction time (1–5 h), temperature (90–180 °C) and sGO dosage (62.5–500 mg in 25 mL reaction volume) on the hydrolysis of pretreated microcrystalline cellulose was experimented. It revealed that the yield of glucose and total reducing sugars and selectivity can reach 454.4 ± 22.20 mg/g, 682.6 ± 30.67 mg/g and 95.5%, respectively, at 150 °C for 3 h using 250 mg sGO. The maximum hydrogen efficiency of 150.0 ± 5.65 mL/g was achieved under optimized conditions, which was 2.2-fold higher than that from the pretreated MCC substrate as control in the absence of sGO (67.3 ± 8.84 mL/g).